Prevalence of Sudden and Unexpected Natural Death due to Diseases of Central Nervous System (Eastern Green Neurosurgery, 2019)
Background: The World Health Organization (WHO) has defined sudden unexpected death as a death, non-violent and not otherwise explained, occurring within 24 hours from the onset of symptoms. This study was performed with the objective to evaluate the different neurological causes of sudden and unexpected death.Methods and materials: this is a cross-sectional analytical study with non-probability consecutive sampling technique over the period of one year. Data were collected, and analyzed using SPSS 20. Data were presented in percentages, and stratifications were used to control the modifiers.Results: There were total 110 autopsies done during the period of one year for sudden and unexpected deaths, among which 19 (17.3%) were deaths due to neurological causes, where 17(89.5%) were males and 2(10.5%) were females. There were 68.43% deaths seen during cold weather. Smoking, alcohol and drug abuse all seems to have higher prevalence among the sudden death due to neurological cause. Most common causes were subarachnoid hemorrhage (58%) followed by ganglionic bleed (26%).Conclusion: Common cause of sudden death due to neurological disease in our study seem to be due to intracerebral hemorrhage where subarachnoid hemorrhage was more common. The deaths were more common during the cold weather and most of them stopped their heart at emergency department during resuscitation.